Karakter Religius Melalui Pendidikan Seni Dalam Ekstrakurikuler Rebana SDN Batu 1 - Muhammad Rizal Rachman; Ari Widyaningrum; Husni Wakhyudin (STKIP Andi Matappa Pangkep, 2021)
The aim of this study was to find out the religious character building through art education in extracurricular rebana in SDN Batu 1. The type of research used is a qualitative method with descriptive approach. In this study, the researcher used several methods to collect the data, such as: interviews, observation, questionnaires, and documentation. The data analysis technique used is the triangulation technique. The results of this study indicate that the religious character building through art education in extracurricular rebana in SDN Batu 1 can be done through art education which is a skill for instance: vocal skills / singing sholawat songs (vocal / voice art). Then, playing rebana musical instruments skills (the art of beating rebana). Then, the process of religious characters building in the playing rebana musical instrument skills, students will develop the ability to beat a rebana musical instrument so that it is in harmony with sholawat songs in order to create a religious atmosphere and can build the religious character of students. Meanwhile, basic dancing skills (dance). The process of religious characters building in basic dancing skills can be seen from the dance movements contained in the rebana extracurricular. The dance movement will build the religious character of the students.